Marketing Ijen-Raung Arabica Coffee Based On Sharia Principles To Enter The International Market - Abel Ayu Malinda; Nurul Huda (CV Putra Publisher, 2026)
Indonesia is one of the world's largest coffee-producing countries, yet the export potential of premium coffee products, including Ijen-Raung Arabica Coffee from Bondowoso, has not been fully realized due to limited domestic market adoption and increasing global competition. This study aims to formulate an effective marketing strategy for Ijen-Raung Arabica Coffee by integrating Sharia principles to enhance its competitiveness in the international market. A qualitative descriptive approach was employed. Data were collected through questionnaires, interviews, observations, documentation, and a literature review conducted in Bondowoso Regency, East Java, and were analyzed using thematic analysis. The findings reveal that an effective international marketing strategy should integrate the marketing mix (product, price, place, and promotion), market segmentation, and target market selection with Sharia marketing principles, including honesty, transparency, fairness, social responsibility, and halal value chain integration. In addition, the distinctive flavor, premium quality, product innovation, continuous quality improvement, product differentiation, and digital marketing strengthen the competitive advantage of Ijen-Raung Arabica Coffee in the global market. The study concludes that integrating Sharia-based marketing principles with product quality enhancement and digital marketing provides an effective strategy for expanding the international market presence of Ijen-Raung Arabica Coffee while maintaining ethical and sustainable business practices